التدفق النفسي وعلاقته بالمرونة النفسية لدى عينة من طلاب جامعة البعث - عز الدين، رازان نديم (جامعه دمشق - كليه التربية, 2022)
هدف البحث إلى تعرف العلاقة بين التدفق النفسي والمرونة النفسية باستخدام مقياس التدفق النفسي "جاكسون ومارش" (1996) ومقياس المرونة النفسية "كونور ودافيدسون" (2003) بعد ترجمتهما ودراسة خصائصهما السيكومترية. تألفت عينة البحث من (800) طالبًا وطالبة اختيروا بالطريقة العشوائية العنقودية (٣٧٦) طالبًا و(٤٢٤) طالبة من طلاب السنة الثانية والثالثة من كليات جامعة البعث، وأظهرت نتائج البحث أن مستوى التدفق النفسي لدى أفراد العينة متوسط، وأن مستوى المرونة النفسية لديهم مرتفع، ووجود علاقة ارتباطية إيجابية بين التدفق النفسي والمرونة النفسية لدى أفراد العينة، وعدم وجود فروق بين متوسطات الدرجات على مقياس التدفق النفسي تبعًا لمتغيرات الجنس والاختصاص، ووجود فروق بين متوسطات الدرجات على مقياس المرونة النفسية تبعًا لمتغير الجنس لصالح الذكور، وتبعًا لمتغير الاختصاص لصالح الكليات النظرية. The aim of the research is to identify the relationship between psychological flow and psychological flexibility. The psychological flow scale "Jackson and Marsh" (1996) and the psychological flexibility scale "Connor and Davidson" (2003) were used after their translation and study of their psychometric properties. The research sample consisted of (800) male and female students who were chosen by the random cluster method (376) males and (424) females students of the second and third year of Al-Baath University colleges, the results of the research showed that members of the research sample have an average level of psychological flow, and that members of the research sample have a high level of Psychological flexibility, and the existence of a positive correlation between psychological flow and psychological flexibility among the members of the research sample, and there are no differences between the mean scores of the sample members on the psychological flow scale according to the variables of gender and specialization, and there are differences between the mean scores of the individuals of the research sample on the psychological flexibility scale according to the gender variable in favor of males, and according to the specialization variable in favor of theoretical colleges.
Keywords: علم النفس الإيجابي -- الصحة النفسية -- التدفق النفسي -- طلبة المرحلة الجامعية -- الجامعات السورية